Pengaruh Metode Latihan dan Koordinasi Mata-tangan Terhadap Keterampilan Smash Bulutangkis - Ella Anugrarista; Arisman Arisman (Jurnal MensSana, 2019)
The purpose of this research was to determine the effect of the drill training methods and tactical training methods and hand-eye coordination skills to badminton smash. Research was done on badminton athletes at Badminton School Camp 43 Pontianak , this study used treatments by level 2 x 2. The sample consisted of 32 athletes were divided into 2 groups, each group has of 16 athletes . The data analysis technique is a two-lane varianas analysis ( ANOVA ) and then followed by Tuckey test at a significance level of significance at α = 0 ,05.The results of this research indicate that ( 1 ) drill exercise methods has a better effect than tactical training methods to badminton smash skills ( 2 ) there is interaction between drill training methods and tactical training methods and hand-eye coordination skills to badminton smash, ( 3 ) exercise drill methods has a better effect than tactical training methods that have high eye-hand coordination.( 4 ) drill exercise method has a better effect than tactical training methods that have low eye-hand coordination.